A Murine Point Mutation of Sgpl1 Skin Is Enriched With Vγ6 IL17-Producing Cell and Revealed With Hyperpigmentation After Imiquimod Treatment - Yang, Wenyi; Zhou, Binhui; Liu, Qi; Liu, Taozhen; Wang, Huijie; Zhang, Pei; Lu, Liaoxun; Zhang, Lichen; Zhang, Fanghui; Huang, Rong; Zhou, Jitong; Chao, Tianzhu; et al. (Frontiers in Immunology, 2022)
Sphingosine-1-phosphate lyase is encoded by the Sgpl1 gene, degrades S1P, and is crucial for S1P homeostasis in animal models and humans. S1P lyase deficient patients suffer from adrenal insufficiency, severe lymphopenia, and skin disorders. In this study, we used random mutagenesis screening to identify a mouse line carrying a missense mutation of Sgpl1 (M467K). This mutation caused similar pathologies as Sgpl1 knock-out mice in multiple organs, but greatly preserved it its life span, which M467K mutation mice look normal under SPF condition for over 40 weeks, in contrast the knock-out mice live no more than 6 weeks. We found that when treated with Imiquimod, Sgpl1M467K mice experienced exacerbated skin inflammation, as revealed by aggravated acanthosis and orthokeratotic hyperkeratosis. We also demonstrated the IL17a producing the V6+ cell was enriched in Sgpl1M467K skin and caused severe pathology after imiquimod treatment. Interestingly, hyperchromic plaque occurred in the mutant mice one month after Imiquimod treatment but not in the controls, which resembled the skin disorder found in SGPL1 deficient patients. Therefore, our results demonstrate that Sgpl1M467K point mutation mice successfully modeled a human disease after treated with Imiquimod. We also revealed that a major subset of γδT cells in the skin, IL17 secreting Vγ6 T cells were augmented by Sgpl1 deficiency and led to skin pathology. Therefore, we have, for the first time, linked the IL17a and T cells to SPL insufficiency.